Development and Implementation of an Inexpensive, Easily Producible, Time Efficient External Ventricular Drain Simulator Using 3-Dimensional Printing and Image Registration. Issue 4 (5th June 2018) - Bow, Hansen; He, Le; Raees, Muhammad Aanish; Pruthi, Sumit; Chitale, Rohan
Abstract: BACKGROUND: External ventricular drain (EVD) placement is one of the most commonly performed procedures in neurosurgery, frequently by the junior neurosurgery resident. Simulators for EVD placement are often costly, time-intensive to create, and complicated to set up. OBJECTIVE: To describe creation of a simulator that is inexpensive, time-efficient, and simple to set up. METHODS: This simulator involves printing a hollow head using a desktop 3-dimensional (3D) printer. This head is registered to a commercially available image-guidance system. A total of 11 participants volunteered for this simulation module. EVD placement was assessed at baseline, after verbal teaching, and after live 3D view instruction. RESULTS: Accurate placement of an EVD on the right side at the foramen of Monro or the frontal horn of the lateral ventricle increased from 44% to 98% with training. Similarly, accurate placement on the left increased from 42% to 85% with training. CONCLUSION: During participation in the simulation, accurate placement of EVDs increased significantly. All participants believed that they had a better understanding of ventricular anatomy and that this module would be useful as a teaching tool for neurosurgery interns.